The United Nations Convention on the Law of the Sea and the marine environment: a contribution to the analysis of the regulation of the protection and preservation of the marine environment in UNCLOS - ZANELLA, Tiago Vinicius (Revista Jurídica Portucalense, 2024)
The central purpose of this paper is to comprehensively analyze how the United Nations Convention on the Law of the Sea (UNCLOS) establishes standards and regulates the protection and prevention of the marine environment. Systematically, the article seeks not only to understand the relevance of UNCLOS for international law but also to highlight its influence on the global legal scenario and for the protection and preservation of the marine environment. The analysis explores the Convention's main attributes and implications for international law, providing a more complete view of its role in the environmental context. By examining the distinctive features of the UNCLOS text, the study investigates its innovations in comparison with other treaties, evaluating their practical applicability. Furthermore, attention is devoted to the complex issue of State sovereignty over natural resources in the maritime context, focusing on avoiding environmental damage to third States and areas beyond its jurisdiction. Thus, this article aims to contribute to a deeper understanding of the impact and effectiveness of UNCLOS in preserving the marine environment and developing international law.